DIFFERENTIATION IN RISK PREFERENCES AMONG SME ACTORS AS CUSTOMER OF CONVENTIONAL MFI VS ISLAMIC MFI AT PADANG - DAVY HENDRI (Maqdis: Jurnal Kajian Ekonomi Islam, 2016)
This study highlights the characteristics of Small and Middle Entrepreneurs (SMEs) as a debtor of micro finance institution (MFI), whether as conventional or sharia type. The study was conducted by taking primary data including 30 debtors of conventional MFI and 29 debtors of Sharia MFI using a questionnaire. In the first stage, the study established several indices to measure the religiosity level using Principal Component Analysis. Additionally, game field experiments use in order to reveal the debtor’s risk preferences. At a later stage, the probit regression model used. This study found that debtors of sharia MFI is relatively more religious. There is also a fact that debtors from both types of MFI have the same risk preferences, risk lover. But debtors in sharia MFI have a relatively lower level one. So, in order to broaden the Sharia MFI inclution, the managers have to pay more attention to at least two other characteristics of SMEs; their age and the years of experience in business management.